Green, practical & scalable approach towards the synthesis of valuable α-keto amides using a metal-free catalyst under solvent-free conditions - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (New Journal of Chemistry, 2023)
alpha-Ketoamides are very important motifs as they are present in many natural products, drugs & biologically important molecules. We synthesized a very simple, cheap, eco-friendly & reusable glucose-based carbonaceous material (GCM), which showed high performance as a catalyst in the oxidative cross-dehydrogenative coupling (CDC) reaction of alpha-ketoaldehydes with amines for the synthesis of alpha-ketoamides. The GCM catalyst was also very efficient for one-pot two-step synthesis of alpha-ketoamides from alpha-ketoalcohols as well. The GCM catalyst was able to catalyze alcohol oxidation in alpha-ketoalcohols followed by CDC reaction with amines to form alpha-ketoalcohols. The reactions were found to proceed smoothly at a low temperature of 50 degrees C using a green & economical metal-free catalyst under base-free, ligand-free & solvent-free reaction conditions to get the corresponding alpha-ketoamides in good to excellent yields. The results demonstrated that the GCM catalyst showed acidic as well as superior oxidising catalytic activity due to the presence of a carboxylic acid (-COOH) and hydroxyl (-OH)-enriched carbonaceous framework, which enabled the synthesis of important alpha-ketoamide motifs. The applicability of the catalyst was also evaluated for the synthesis of an anti-HIV agent drug molecule. Greener, cheaper & eco-friendly GCM catalyst as well as catalytic process for synthesis of alpha-Keto Amides.

Graphitic-C3N4/γ-Al2O3 composite catalyst for synthesis of 5-(Hydroxymethyl) furfural from d-Glucose - Kirdant, Swapnali P.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Energy & Fuels, 2025)
Currently, the synthesis of 5-hydroxymethylfurfural (5-HMF), with high yields and selectivity from different renewable sources, is an important focus in the biomass conversion area. In the present study, a g-C3N4/gamma-Al2O3(1:1) composite catalyst was prepared using graphitic carbon nitride (g-C3N4) and acidic gamma-alumina (gamma-Al2O3), which was evaluated for its catalytic activity in converting sugars, mainly glucose, to 5-HMF. In the g-C3N4/gamma-Al2O3(1:1) catalyst, N-containing groups on g-C3N4 provided basicity and gamma-Al2O3 provided Lewis acidity to the catalyst. The g-C3N4/gamma-Al2O3(1:1) composite catalyst showed superior activity for 5-HMF synthesis compared to gamma-Al2O3 and g-C3N4 alone. The increased acidic and basic properties of the g-C3N4/gamma-Al2O3(1:1) catalyst significantly influenced both glucose-to-fructose isomerization and dehydration of fructose to HMF by increasing the yield of 5-HMF. In addition, the solvent DMSO:water also played an important role in the one-pot conversion of glucose to HMF by minimizing side reactions, which significantly improved the 5-HMF yield. The reaction was optimized for various solvents, temperatures, and catalyst concentrations to get a maximum yield of 91% from glucose with >99% selectivity of crude 5-HMF. Other sugars like fructose, sucrose, and lactose also provided good yields of 5-HMF. The g-C3N4/gamma-Al2O3(1:1) catalyst was stable and was effectively reused for up to four cycles.